Clinical characteristics of children hospitalized with cellulitis in Spain (2016–2022). A population-based analysis - Belinchón-Romero, Isabel; Ramos-Rincón, José-Manuel (Frontiers in Pediatrics, 2025)
AimTo estimate hospitalization rates, describe clinical characteristics, and assess the direct healthcare costs of cellulitis-related hospitalizations in children of different ages: 0–4 years, 5–9 years, and 10–14 years.Materials and methodsThis retrospective, population-based study included patients aged 14 years or less and hospitalized for cellulitis in Spain between 2016 and 2022. Data were obtained from the Spanish Registry of Specialist Care Activities provided by the Ministry of Health.ResultsA total of 15,497 cellulitis-related hospitalizations were included: 7,378 (47.6%) aged 0–4 years, 4,532 (29.2%) aged 5–9 years, and 3,587 (23.1%) aged 10–14 years. The proportion of boys (56.6%) was higher than for girls and increased with age (p < 0.001). The most common anatomical site was the extremities (excluding fingers and toes), comprising 40.9% of cases, with frequency increasing with age (p < 0.001). Facial cellulitis was the second most frequent site (37.4%), but its proportion decreased with age (p < 0.001). The main predisposing factors for infection were trauma and open wounds (13.5%), especially in older children (p < 0.001), along with atopic dermatitis (3.1%). Only 2.8% of children required intensive care unit (ICU) admission, with the highest rates in the youngest group and the lowest in the 5–9-year-old group. In-hospital mortality was consistently low (0.1%) across age groups. The total direct cost of hospitalizations was estimated at €54.7 million: €28.2 million in 0–4-year-olds, €13.7 million in 5–9-year-olds, and €12.8 million in 10–14-year-olds.ConclusionsThe clinical profile of cellulitis varies by age group. While ICU admission and in-hospital mortality were rare, the economic burden remains substantial, particularly among younger children.